2022
DOI: 10.1097/shk.0000000000002043
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variants and Serum Profiles of Cytokines in Covid-19 Severity

Abstract: Background: Patients with severe coronavirus disease 2019 (COVID-19) are at an increased risk of acute respiratory distress syndrome and mortality. This is due to the increased levels of pro-inflammatory cytokines that amplify downstream pathways that are controlled by immune regulators. Objective: This study aimed to investigate the association between cytokine genetic variants, cytokine serum levels/profiles, and disease severity in critically and noncritically ill COVID-19 patients. Methods: This cross-sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Single‐nucleotide polymorphism rs8071286 of CXCL16 gene was found to be associated with the COVID‐19 critically ill phenotype (OR A = 1.42 (95% CI: 1.41, 1.44); p = 0.018). This study suggests that CXCL16 could be used as a potential biomarker for monitoring disease progression of COVID‐19 patients 33 …”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…Single‐nucleotide polymorphism rs8071286 of CXCL16 gene was found to be associated with the COVID‐19 critically ill phenotype (OR A = 1.42 (95% CI: 1.41, 1.44); p = 0.018). This study suggests that CXCL16 could be used as a potential biomarker for monitoring disease progression of COVID‐19 patients 33 …”
Section: Discussionmentioning
confidence: 80%
“…Alefishat et al's 33 work found that CXCL16 serum level was significantly higher among critical COVID‐19 patients when comparing with noncritically ill COVID‐19 patients.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…126,127 Concomitantly, the rs1554606 SNP was also associated with severe COVID-19 patients, and there was an association of IL-6 gene expression at serum levels also in cases of disease severity. 128…”
Section: Introductionmentioning
confidence: 99%